Right-Sided Heart Failure Presentation in Severe Valvular Aortic Stenosis: How to Deal with Diuretic Use? - Fahmy Rusnanta; Cholid Tri Tjahjono; Anna Fuji Rahimah; Heny Martini (Universitas Brawijaya, 2021)
BACKGROUND: Patients with right-sided heart failure and severe aortic stenosis (AS) have many clinical challenges to overcome fluid retention. Typical diuretic therapeutic approach can be recommended for the guidance of removing fluid overload in severe AS with right ventricular (RV) failure. The aim of this case review is to understand how to assess and manage RHF and severe AS. CASE SUMMARY: A 65-year-old female with worsening bilateral leg swelling and she aware of shortness of breath for 3 months. Physical examination revealed a grade 3/6 ejection systolic murmur at the aortic area radiating to the neck, a grade 2/6 diastolic murmur at the pulmonic area, and a grade 3/6 systolic murmur at the apex radiating to the axilla, increased jugular venous pressure, prominent bilateral leg swelling, and minimal rhonci at the base of the lungs. The chest X-ray showed worsening cardiomegaly in the last 3 months. Echocardiography revealed high gradient severe valvular AS, decreased systolic RV function, and other valvular dysfunctions including moderate mitral regurgitation, moderate pulmonary regurgitation, and mild tricuspid regurgitation. She was introduced high dose furosemide infusion. The average urine output production was 5 L/day and negative fluid balance was 3 L/day. Furosemide dose was adjusted daily according to urine output production and she was discharged after 6 days hospitalization. DISCUSSION: This case report provides an example of RV failure in severe AS patient. Hemodynamic monitoring and typical approach of diuretic therapies should be needed in the management of fluid overload in severe AS. KEYWORDS: right-sided heart failure, severe aortic stenosis, diuretic.